(untitled) (Hoboken, N.J., 2006)
This book provides a solid theoretical framework, along with detailed, practical guidance on use of GFPs and NFPs with discussion of potential pitfalls. The expert contributors provide real examples in showing how to tailor GFP/NFP to specific systems, maximize expression, and enhance detection
Keywords: Green fluorescent protein,Đạm phát quang sinh học